2016
DOI: 10.1007/s00214-015-1795-3
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular perturbation in the self-assembly of melamine

Abstract: charge density descriptors were used to evaluate the aromaticity of M in each complex. Results show that the hydrogen and halogen (XBs) bond interactions, which direct the self-assembly process in these complexes, are anti-cooperative. Binding energies decrease in the following order: M/ (CA) n > M/(TCA) n > M/(CABr) n > M/(CACl) n (for all values of n). Brominated CA arises as a potential compound to self-assembly with M via XBs. Keywords Cyanuric acid • Supramolecular • Molecular building blocks • Hydrogen b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…In fact, and to the best of our knowledge, only a single study has been reported that considers a graphitic carbon nitride (g-C 3 N 4 )based building block as a XB acceptor. 33 g-C 3 N 4 s are dense two-dimensional crystalline materials that are typically investigated for their promising metal-free electrochemical and photocatalytic properties. 34,35 In the work of Sosa and coworkers, 33 the authors probe the NCIs formed between either chlorinated or brominated cyanuric acid and melamine (i.e., melamine/(CACl) n=1−3 and melamine/(CABr) n=1−3 ).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, and to the best of our knowledge, only a single study has been reported that considers a graphitic carbon nitride (g-C 3 N 4 )based building block as a XB acceptor. 33 g-C 3 N 4 s are dense two-dimensional crystalline materials that are typically investigated for their promising metal-free electrochemical and photocatalytic properties. 34,35 In the work of Sosa and coworkers, 33 the authors probe the NCIs formed between either chlorinated or brominated cyanuric acid and melamine (i.e., melamine/(CACl) n=1−3 and melamine/(CABr) n=1−3 ).…”
Section: ■ Introductionmentioning
confidence: 99%
“…33 g-C 3 N 4 s are dense two-dimensional crystalline materials that are typically investigated for their promising metal-free electrochemical and photocatalytic properties. 34,35 In the work of Sosa and coworkers, 33 the authors probe the NCIs formed between either chlorinated or brominated cyanuric acid and melamine (i.e., melamine/(CACl) n=1−3 and melamine/(CABr) n=1−3 ). Through a series of bond critical point and pathway analyses based on the total electron density, the authors discovered that the chlorine-containing complexes generally consist of only Cl•••N XB interactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This method has proved to show a great performance in similar systems. [32][33][34] The minimum energy nature of the optimized structures was verified using the vibrational frequency analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, an increasing interest in nanoscale devices has stimulated the research of intra- and intermolecular forces that control and lead to the creation of ordered one-, two-, and three-dimensional nanostructures from the self-assembly of small molecular building blocks by using hydrogen bonds and π–π interactions. Melamine has an immense contribution in this field due to its structural functionalizm . Seto et al developed a methodology to construct large, soluble, self-assembling structures based on the hydrogen-bonded complex by introducing melamine with the determination of enthalpy of formation and entropy of solvation of the complex.…”
Section: Introductionmentioning
confidence: 99%
“…Melamine has an immense contribution in this field due to its structural functionalizm. 8 Seto et al 9 developed a methodology to construct large, soluble, self-assembling structures based on the hydrogen-bonded complex by introducing melamine with the determination of enthalpy of formation and entropy of solvation of the complex. Vella-Zerb et al 10 and Shen et al 11 separately showed that the hydrogen bond interactions between melamine and other molecules forces melamine to crystallize in layers using melamine as one of the main building blocks.…”
Section: Introductionmentioning
confidence: 99%